Towards a population synthesis model of self-gravitating disc fragmentation and tidal downsizing II: the effect of fragment–fragment interactions. Issue 4 (9th November 2017) - Forgan, D H; Hall, C; Meru, F; Rice, W K M
Abstract: It is likely that most protostellar systems undergo a brief phase where the protostellar disc is self-gravitating. If these discs are prone to fragmentation, then they are able to rapidly form objects that are initially of several Jupiter masses and larger. The fate of these disc fragments (and the fate of planetary bodies formed afterwards via core accretion) depends sensitively not only on the fragment's interaction with the disc, but also with its neighbouring fragments. We return to and revise our population synthesis model of self-gravitating disc fragmentation and tidal downsizing. Amongst other improvements, the model now directly incorporates fragment–fragment interactions while the disc is still present. We find that fragment–fragment scattering dominates the orbital evolution, even when we enforce rapid migration and inefficient gap formation. Compared to our previous model, we see a small increase in the number of terrestrial-type objects being formed, although their survival under tidal evolution is at best unclear. We also see evidence for disrupted fragments with evolved grain populations – this is circumstantial evidence for the formation of planetesimal belts, a phenomenon not seen in runs where fragment–fragment interactions are ignored. In spite of intense dynamical evolution, our population is dominated by massive giant planets and brown dwarfs at large semimajor axis, which direct imaging surveys should, but only rarely, detect. Finally, disc fragmentation is shown to be an efficient manufacturer of free-floating planetary mass objects, and the typical multiplicity of systems formed via gravitational instability will be low.